Characterization of green Al2O3 ceramics surface machined by tools with textures on flank‐face in dry turning. Issue 3 (4th February 2019) - Liu, Yayun; Deng, Jianxin; Wang, Wei; Duan, Ran; Xing, Youqiang
Abstract: Green Al2 O3 ceramics through cold isostatic pressing were produced. Scratch tests were performed to evaluate the machinability. Texturing was applied on the flank‐face of the WC/Co tools by laser. Tools with textures on the flank‐face were adopted in dry cylindrical turning of the green Al2 O3 ceramics. Characterization of green ceramic surfaces machined by flank‐face textured tools was studied. Results revealed that green ceramics had good enough machinability in cutting tests and scratch tests. There were no visible cracks on the surface after machining. Flank‐face textured tools could improve the surface integrity during processing green Al2 O3 ceramics. Mechanisms responsible were found that derivative‐cutting behavior by flank‐face textures was able to remove visible hard inclusions on surfaces of green ceramics, which made the surfaces much smoother. More tiny ceramic powders generated by the phenomenon were pressed on the surfaces of green ceramics, which made further efforts on improving surface quality. Machining parameters had significant impacts on surface integrity. Within machining parameters, surface quality became better and compaction area was found on surfaces of green Al2 O3 ceramics with the increase of cutting depth, but there were still visible hard inclusions and spalling of materials on the surface after machining.